HUBUNGAN DUKUNGAN SUAMI SAAT ANTENATAL DAN INTRANATAL DENGAN BOUNDING ATTACHMENT PADA IBU POST PARTUM DI RSU PANCARAN KASIH GMIM MANADO - Awalla, Sriniwandi; Kundre, Rina; Rompas, Sefty (JURNAL KEPERAWATAN, 2015)
Abstrack: During pregnancy a wife needs a pair of support that comes from the husband. Husband to the mother's lack of support will lead to not nurture drope affection between mother and baby or not nurtured bounding attachment to mother and baby. The purpose of this study was to determine the relationship of husband support during antenatal and intranatal with bounding attachment on post partum mothers at General Hospital Pancaran Kasih GMIM Manado. The design of this research was descriptive analytic cross sectional design. Samples were taken through out the post partum mothers in pavilium Maria at General Hospital Pancaran Kasih GMIM Manado numbered 34 people with the sampling technique was total sampling. The results of this study was the relationship of support from husband during antenatal with the bounding attachment obtained significant P value = 0.001 mean P value <0.05 and during intranatal with bounding attachment obtained P value = 0,037 mean P value <0,05. So it can be concluded that there is a relationship of husband support during antenatal and intranatal with bounding attachment on post partum mothers at General Hospital Pancaran Kasih GMIM Manado. This research was expected to provide antenatal and intranatal support to the wife in order to create a bounding attachment as early as possible. Keywords: Husband Support, BoundingAttachment Abstrak: Pada masa kehamilan seorang isteri membutuhkan suatu dukungan yang bersumber dari pasangan yaitu suami. Kurangnya dukungan suami ke ibu akan mengakibatkan tidak terbina ikatan tali kasih sayang antara ibu dan bayi atau tidak terbina bounding attachment pada ibu dan bayi. Tujuan dari penelitian ini untuk mengetahui hubungan dukungan suami saat antenatal dan intranatal dengan bounding attachment pada ibu post partum di RSU Pancaran Kasih GMIM Manado. Desain penelitian yang digunakan adalah deskriptif analitik dengan rancangan cross sectional. Sampel penelitian ini adalah seluruh ibu post partum di Pavilium Maria RSU Pancaran Kasih GMIM Manado berjumlah 34 orang dengan teknik pengambilan sampel adalah total sampling. Hasil penelitian hubungan dukungan suami saat antenatal dengan bounding attachment didapatkan P value = 0,001 berarti P value< 0,05 dan hubungan dukungan suami saat intranatal dengan bounding attachment didapatkan P value = 0,037 berarti P value< 0,05. Sehingga dapat disimpulkan bahwa ada hubungan dukungan suami saat antenatal dan intranatal dengan bounding attachment pada ibu post partum di RSU Pancaran Kasih GMIM Manado. Penelitian ini diharapkan bagi para suami untuk memberikan dukungan saat antenatal dan intranatal kepada isteri agar tercipta bounding attachment sedini mungkin. Kata Kunci: Dukungan Suami, Bounding Attachment